LDL particle heterogeneity, and its association with other established cardiovascular risk factors in a young Indian industrial population. Issue 1 (16th October 2012) - Lakshmy, Ramakrishnan; Dorairaj, Prabhakaran; Tarik, Mohamad; Gupta, Ruby; Reddy, Kolli Srinath
Abstract : Objective: Low density lipoprotein (LDL) particles are heterogeneous in terms of size, density, chemical composition and electric charge with certain particle of LDL being more atherogenic than the others. The present study aimed to look at the LDL particle heterogeneity, particle size and association with other cardiovascular disease (CVD) risk factors in young Indian industrial population. Methodology: 600 employees of an industry of Delhi, aged 20-39 years were selected for the study. Data on demographics, individual characteristics associated with major risk factors of CVD, past medical history, clinical and anthropometric profile was collected. Fasting glucose, lipid profile, apolipoprotein (A1, B, and E), lipoprotein (a), high sensitive C-reactive protein (hsCRP) and insulin were estimated. LDL particle size was determined in ethylenediamminetetraacetate (EDTA) plasma by 3% polyacrylamide gel electrophoresis. Result: We found a prevalence of small dense LDL phenotype (LDL size ≤ 26.3) in 27.4% of males and 24.0% of females. The mean waist circumference, blood pressure, triglycerides (TAG), cholesterol, hsCRP, apolipoprotein (A1, B and E) and insulin were higher in males whereas mean high density lipoprotein was higher in females. Females also had a significantly higher mean LDL particle diameter as compared to males. Conclusion: TAG, physical activity and lipoprotein (a) correlated with small dense LDL in this young Indian population.